Legal Analysis on Status as A Co-Defendant Notary in Dispute of Gather Treasure (Case Study in The Court of Ungaran District No: 105 / Pdt.G / 2016 / PN.Unr) - Rudy Iskandar Ichlas; Akhmad Khisni (Jurnal Akta, 2019)
Authentic Deed is not solely determined by the law but must also be made before a public official even though the parties have signed. Pernasalahan formulation of this research: 1. How plaintiff legal reasons related to the notary as a co-defendant in the decision number 105 / Rev. G / 2016 / PN. Unr ?, 2. What legal consequences for the Notary as a co-defendant in the decision number 105 / Rev. G / 2016 / PN. Unr. In conclusion: 1). Position Anief Ratnawati, SH, Notary / PPAT in Ungaran as Co-Defendant extremely detrimental due to the lack of legal certainty as Co-Defendant and One goal (error in persona). Hence proved their obscuur libel and Error In Persona judge shall include in its decision to declare the judgment can not receive (NO: Niet ontvankelijk verklaard) lawsuit plaintiffs, 2). Anief Ratnawati, SH. as a Notary Public who is drawn into the dispute be imprecise Co-Defendant not authorized in terms of time (Onbevoegdheid ratione Temporis) and violates the principle of legality and the principles of civil law as private law. On the other hand the plaintiff proved to be an inheritance dispute within the competence of religious courtsKeywords: Legal Analysis; Notary; Co-defendant; Dispute; Gather Treasure.